Technology readiness, information and communication technology (ICT) competency, and the nature and pattern of ICT utilizing among nurses of a tertiary hospital - Formoso, Juanito H. Jr
This study aimed to develop a technology integration profile among nurses, which will contribute to the development of a knowledge base that will facilitate the understanding of ICT integration within the Philippine healthcare delivery system especially on a nursing perspective. Elements of this profile includes the technology readiness level, ICT competency level and the relationship of these constructs with the nature and pattern of ICT utilization among nurses.